2008
DOI: 10.1167/iovs.07-0856
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Conjunctiva-Associated Lymphoid Tissue of the Rabbit

Abstract: Age-related changes in rabbit O-CALT are similar to those that have been reported for the human conjunctiva. Preferential uptake of latex beads by follicle-associated epithelium indicates that the presence and function of M cells are not affected by aging. The lower level of O-CALT in young and elderly animals, however, would be expected to decrease their ocular mucosal immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 24 publications
4
31
0
Order By: Relevance
“…7 In the present study, we did not find significant differences in follicular parameters between males and females. These results seem to be in agreement with those reported in rabbits, 30 where from adolescence, the number of follicles in males and females is similar (females presented 1% fewer follicles than males). Previous histological studies in humans were not reported.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…7 In the present study, we did not find significant differences in follicular parameters between males and females. These results seem to be in agreement with those reported in rabbits, 30 where from adolescence, the number of follicles in males and females is similar (females presented 1% fewer follicles than males). Previous histological studies in humans were not reported.…”
Section: Discussionsupporting
confidence: 92%
“…6,7 Similar modifications were reported in rabbits, where the number of follicles increased until adolescence, stabilized through early adulthood, and dramatically declined in elderly rabbits. 30 In our study, information from the pre-pubertal period, when lymphoid structures present a florid developing phase, lack. For the rest of life, our results were in line with literature concerning follicle density, which showed an evident decline with age, 12 but appeared opposite concerning follicular size, because area decreased.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…100 nm) seems therefore inappropriate to investigate M cells specifically. In contrast, latex beads and bacteria were demonstrated to be transported across the conjunctival FAE by specialized cells [41,47,52] . Following the postulate of the authors mentioned above, the basic conditions for the identification of M cells in the conjunctival FAE of rabbits, guinea pigs and dogs are fulfilled.…”
Section: Functional Studies Of Caltmentioning
confidence: 96%
“…Substances or particles that were used in studies of conjunctival FAE and M cells include latex microspheres (0.2-2.9 m in diameter) [43,46,47] , lectins ( Maackia amurensis leukoagglutinin I) [48] , horseradish peroxidase [49] , carbon and iron oxide [50,51] and bacteria (heat-killed Staphylococcus aureus , nontypeable Haemophilus influenzae ) [41,52] . These tracers were topically applied onto the ocular surface of rabbits (iron oxide, latex beads), guinea pigs (lectin, horseradish peroxidase and bacteria), chickens and turkeys (carbon and iron oxide, latex beads) and dogs (bacteria).…”
Section: Functional Studies Of Caltmentioning
confidence: 99%